PARTISIPASI PRIA DALAM PROGRAM KELUARGA BERENCANA (KB) - Reno Muhatiah (Marwah: Jurnal Perempuan, Agama dan Jender, 2012)
This article discusses the factors influence man participation in family planning program by using Preced of Green Behavioral Approach. The limited man participation in family planning because of the factor of predisposing actors which consist of knowledge, attitude, confidence, value, curltural, and perception, with reference to someone motivation or group to act. Enabling factors like personal or community resource and skill. The reinforcing factors is the determining factor whether the health action obtained support or not. This factor is a represent factor (incoming after) like attitude and behavior of elite community, religion figure, behavior and attitude all the officer including officer of health.